Orion reveals acquisition of French carbon black producer; posts strong sales gain in 3Q 2018. Issue 12 (December 2018) - Unknown
Abstract : Carbon black manufacturer Orion Engineered Carbons has acquired Société du Noir d'Acétylène de l'Aubette (SN2A) from LyondellBasell Industries Holdings and its French affiliate for an undisclosed sum. Founded in 1987 and headquartered at Berre l'Etang, near Marseille, France, SN2A is a producer of acetylene black. The transaction closed on 31 October 2018 with SN2A, now renamed Orion Engineered Carbons France SAS, operating as a subsidiary of Orion since that date. The acquisition enhances Orion's product portfolio and expertise.